KONSEP PENDIDIKAN MULTIKULTURAL BERBASIS KARAKTER: KAJIAN SURAT AL HUJURAT AYAT 13 PERSPEKTIF IBNU KATSIR - Karuniawan, Iing Ilham; Yusuf, Enjang Burhanudin (Atthiflah: Journal of Early Childhood Islamic Education, 2024)
The diversity of ethnicities, cultures and languages that exist in Indonesia is a clear example of the benefits of a pluralistic society. However, there is a risk of conflict here which could endanger the continuity of the country. This can be seen in a number of areas affected by conflict in Indonesia, including Sampit (between the Madurese and Dayak tribes), Poso (between Christians and Muslims), Aceh (between GAM and the Republic of Indonesia), and student brawls between schools. and frequent fights between villages in various regions of Java. This research uses library research to explore the concept of character-based multicultural education. In this research, there is use, namely the use of reading materials, reference books, or other research results to discover, analyze, and improve one's understanding of literary works. Research findings in Surah Al-Hujurat verse 13 include getting to know each other, tolerance, and developing devotion to Allah SWT.